Integration of transplanted hepatocytes into host liver plates demonstrated with dipeptidyl peptidase IV-deficient rats. - Gupta, S (1995)
To analyze mechanisms of liver repopulation, we transplanted normal hepatocytes into syngeneic rats deficient in dipeptidyl peptidase IV activity. When isolated hepatocytes were injected into splenic pulp, cells promptly migrated into hepatic sinusoids. To examine whether transplanted hepatocytes entered liver plates and integrated with host hepatocytes, we analyzed sharing of hepatocyte-specific gap junctions and bile canaliculi. Colocalization studies showed gap junctions uniting adjacent transplanted and host hepatocytes in liver plates. Visualization of bile canalicular domains in transplanted and host hepatocytes with dipeptidyl peptidase IV and ATPase activities, respectively, demonstrated hybrid bile canaliculi, which excreted a fluorescent conjugated bile acid analogue. These results indicate that transplanted hepatocytes swiftly overcome mechanical barriers in hepatic sinusoids to enter liver plates and join host cells. Integration into liver parenchyma should physiologically regulate the function or disposition of transplanted hepatocytes and benefit applications such as gene therapy.